Bałtyckie dzieje Europy: prawdy i zmyślenia - Kuzborska, Alina (Przegląd Wschodnioeuropejski, 2024)
The subject of this article is a review of the work of Lithuanian pseudo-historians on alleged misinterpretations of European history in the early Middle Ages, resulting from translation errors of 19th-century German historiography. According to Lithuanian Venezuelan researcher J. Statkutė de Rosales, the origin of the misunderstandings was a mistranslation of a passage from Jordanes’ work Getica. The German translation implied that Goths (Germans) who came from Gotland colonized the southern coast of the Baltic Sea. Statkutė de Rosales assumes that the Goths, or Gudas (lit. gudai), were a Baltic people, living on the continent from time immemorial, their command center was Gothiscandza, or present-day Gdansk, and the Baltic Ostrogoths and Visigoths not only conquered Rome, but also colonized the Iberian peninsula. Statkutė de Rosales used linguistic tools, and by ‘correcting’ the translation offered a new interpretation of history to prove the thesis of the Baltic roots of Europe.